The effects of psychosocial aftercare following pediatric chronic pain treatment withstand the coronavirus disease 2019 pandemic: long-term outcomes of a randomized controlled trial - Lisa-Marie Rau; Meltem Dogan; Gerrit Hirschfeld; Markus Blankenburg; Michael C. Frühwald; Rosemarie Ahnert; Sarah Braun; Ursula Marschall; Boris Zernikow; Julia Wager (PAIN Reports)
Abstract. Introduction:. Intensive interdisciplinary pain treatment (IIPT) is the best therapy available for children and adolescents affected by severe chronic pain. Psychosocial aftercare (PAC) offered for 6 months after IIPT can improve treatment outcomes for up to 12 months. Objectives:. The current study is the first to explore whether PAC is superior to treatment as usual at a long-term follow-up of 18 to 33 months after discharge—including when facing the coronavirus disease 2019 (COVID-19) pandemic. Methods:. A multicenter randomized controlled trial investigated the impact of PAC with follow-up assessments in 2021 during the COVID-19 pandemic (N = 209). Multilevel models and regression analyses explored long-term treatment effects on pain characteristics and psychological outcomes, associations of pandemic-related burden with these outcomes, and whether pandemic-related burden moderates those effects. Results:. Patients who received PAC significantly improved treatment outcomes concerning pain characteristics and psychological well-being 18 to 33 months after IIPT discharge. A COVID-19 infection among family members or peers was associated with a lower probability of having chronic pain at long-term follow-up, whereas having missed or rescheduled health care appointments was associated with a higher probability. Positive evaluations of family time during the pandemic were associated with better psychological well-being. Regardless of pandemic-related burdens, PAC had similarly better outcomes than treatment as usual. Only for anxiety, greater burdens mitigated the advantages of PAC. Conclusion:. Despite adverse circumstances, PAC retained its superiority long-term. Integrating PAC into routine health care to support families after IIPT should be prioritized to yield enduring treatment effects, acting as a buffer against the impacts of unpredictable adverse events.